Career advancement: does gender make a difference? - Newman, Meredith Ann (1993)
Barriers to women's advancement in the public sector continue to be very real. Debate has shifted from concern about equal employment opportunity and access to entry and middle-level leadership positions to an examination of the glass ceiling phenomenon, which prevents many women from reaching upper level management positions. Using a conceptual and analytical framework developed for my doctoral dissertation and data generated from a survey of 253 upper level administrators in the Florida State government, this paper compares the experiences of women to those of men in elite public management positions. The paper underscores the barriers women encounter as they attempt to advance their careers and argues that it is not gender difference, but rather the difference that gender makes that explains why these barriers persist. - Reproduced
Keywords: Civil service